Brand loyalty in Turkish soccer: assesing the relationship between brand associations and brand loyalty - Salman, Gülberk Gültekin (My University, 2005)
Bu çalışma, profesyonel Türk futbolundaki sadakat ve çağrışımların arasındaki ilişkiyi incelemektedir. Çalışma, 2001 yılında Gladden ve Funk'ın Amerika'da yapmış oldukları profesyonel sporlardaki (bu çalışma spor ayırt etmemiştir) sadakat ve çağrışımları inceledikleri çalışmadan esinlenilmiştir. Aaker'in (1996) marka değerinin kavramsal çatısısından esinlenerek Keller'in (1993) marka çağrışımları modelini baz alarak 16 adet (başarı, star oyuncu, antrenör, yönetim, logo, stadyum, ürün sunuşu, gelenek, kaçış, taraftar özdeşleşmesi, akran grup kabullenmesi, nostalji, gurur, önem, bilgi, ve etkilenme reaksiyonu) marka çağrışımı kullanılmıştır. Marka sadakati için hem tutumsal hem de davranışsal sadakat ölçümlenmiştir. Veriler, üç büyük takım olan Galatasaray, Fenerbahçe ve Beşiktaş'ın 594 taraftarından toplanmıştır. Çoklu regresyon analizi marka çağrışımları ve sadakat arasındaki ilişkiyi anlamak için uygulanmıştır. Sonuçlar, 16 çağrışımın, %55 varyans ile sadakati açıkladığını göstermiş ve dokuz çağrışımın anlamlı olarak sadakate bağlı olduğu ortaya çıkarılmıştır. Bu çağrışımlardan gurur negatif, star oyuncu, logo, stadium, kaçış, akran grup kabullenmesi, nostalji, önem ve bilgi pozitif ilişkilerinin bulunduğu ortaya çıkmıştır. Bulguların ışığında, futbol yöneticilerine markalarını yönetmelerinde yön verecek spor pazalarma strateji önerileri sunulmaktadır. This study focuses on brand loyalty and brand associations in professional sport- Turkish soccer, where the relationship between associations and loyalty is essentially assessed. The study primarily is inspired from Gladden and Funk (2001) where they examined the link between associations and loyalty in professional sport in USA, without distinguishing between sports and clubs. Drawing upon Aaker's (1996) conceptual framework on brand equity, a set of 16 brand associations (success, star player, head coach, management, logo, stadium, product delivery, tradition, escape, fan identification, peer group acceptance, pride, nostalgia, importance, knowledge, and affective reactions) are used by relying primarily on Keller's (1993) conceptual model to identify brand associations. Both attitudinal loyalty (possession of a favorable attitude toward the team and the club) and behavioral loyalty (attendance or following the team through the media) are utilized to create a brand loyalty measure. Data are collected from 594 fans, who already support the team and consider themselves as a fan of the three major football clubs in Turkey - Galatasaray, Fenerbahceö and Besiktas. A series of multiple regression analyses are undertaken to examine the relationship between the associations and the loyalty. The findings showed that the adjusted R2 statistics revealed that the 16 dimensions explained 55% of the variance (R2 = .551) that occurs in loyalty. Nine of the 16 dimensions are significantly linked to brand loyalty. Pride, with negative relationship, and star player logo, stadium, escape, peer group acceptance, nostalgia, importance, and knowledge with positive relationship predicts loyalty. Implications of marketing strategies and policies for sport marketers in their efforts to manage their brand (the team and the club) are provided.
Keywords: Genel yönetim; Pazarlama; Pazarlama yönetimi; Üretim Yönetimi